Pengaruh Metode Student-Centered Learning Dalam Pembelajaran Bahasa Arab - Bambang Hermanto; Siful Arifin (Institut Kariman Wirayudha Sumenep, 2023)
This article will discuss the influence of the Student Centered Learning method in learning Arabic. This method has become a subject of interest in the world of education because of its potential to increase student engagement and learning achievement. The research methods used include experimental or testing designs with a control group and an experimental group. The results of this research show that the use of the Student-Centered Learning method in the Arabic language learning process has a significant positive impact on students' understanding. This research makes an important contribution to our understanding of the importance of student-focused learning approaches, and teachers are advised to use this method in an effort to improve students' Arabic learning outcomes.